145 A Cost-Effectiveness Comparison Between Open Transforaminal and Minimally Invasive Lateral Lumbar Interbody Fusions Using the Incremental Cost-Effectiveness Ratio at 2-Year Follow-up. (August 2015) - Gandhoke, Gurpreet Surinder; Shin, Han-Moe; Chang, Yue-Fang; Tempel, Zachary J.; Okonkwo, David O.; Gerszten, Peter C.; Kanter, Adam S.
Abstract : INTRODUCTION: Both transforaminal lumbar interbody fusion (TLIF) and lateral lumbar interbody fusion (LLIF) are effective surgical interventions for patients with degenerative lumbar spondylosis. We sought to compare health care costs by calculating the incremental cost-effectiveness ratio and, thereby, the difference in the total cost per quality-adjusted life-year (QALY) gained for TLIF vs LLIF for the treatment of degenerative spondylosis. We further calculated the thresholds for minimum clinically important difference (MCID) and minimum cost-effective difference (MCED) for patient-reported outcome measures at 2-year follow-up. METHODS: Forty-five patients who underwent single-level TLIF and 29 patients who underwent single-level stand-alone LLIF for degenerative spondylosis with low back and leg pain were included. All costs from diagnosis through 2-year postsurgical follow-up were available from a comprehensive single-center data bank within a unified hospital system. Total cost to the third-party payer for all spine-related medical resource use from the time of diagnosis through 2 years was recorded. QALYs were calculated from EQ-5D collected in an unbiased manner by a nonclinical staff member. Difference in total cost per QALY gained for LLIF minus that for TLIF was assessed as the incremental cost-effectiveness ratio. RESULTS: Significant improvements were observed at 2-year follow-up for both TLIF and LLIF utilizing SF36PCS, ODI, VAS BP, VAS LP, and EQ-5D. Incremental cost-effectiveness ratio (ICER) calculations revealed similar mean cumulative QALYs gained at the 2-year interval (0.67 for TLIF and 0.60 for LLIF; P = .331). Median total cost of care following TLIF and LLIF was $44 068 and $45 574, respectively; ( P = .960). MCED thresholds with an anchor of <$50 000/QALY were higher than MCID thresholds for all patient-reported outcome measures. Total mean cost and EQ-5D were statistically equivalent between the 2 treatment groups. CONCLUSION: TLIF and LLIF produced equivalent 2-year patient outcomes at an equivalent cost-effectiveness profile.